2023
DOI: 10.1101/2023.08.09.23293892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of sepsis recognition on telemedicine use and bundle completion in rural emergency department sepsis treatment

Abstract: Objective: Sepsis has high mortality, but it is often not recognized due to varied and vague presentations. Provider-to-provider emergency department telehealth (tele-ED) has been proposed to improve rural sepsis care, but we hypothesized that its use and effectiveness is dependent on local sepsis recognition. The objective of this study was to measure the association between sepsis documentation and tele-ED use, treatment guideline adherence, and mortality. Methods: This analysis was a multicenter (n=23) coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…20, 21 An early study showed that telehealth in rural EDs was associated with higher sepsis bundle adherence (adjusted odds ratio [aOR] 17.3, 95% confidence interval [CI] 6.6 to 44.9) 22 , but we subsequently found that one significant barrier to telehealth use was sepsis diagnosis and recognition. 23 In another multicenter study in telehealth-capable hospitals with contemporary controls (n=1,191), we found telehealth consultation was not associated with improved outcomes, but the subgroup of patients treated in the most remote hospitals by advanced practice providers may have had reduced mortality (aOR 0.11, 95% CI 0.02 to 0.73). 24 Since these findings were unexpected, we conducted a qualitative study of rural hospital and hub healthcare staff to better understand and interpret the findings from our quantitative studies.…”
Section: Introductionmentioning
confidence: 72%
“…20, 21 An early study showed that telehealth in rural EDs was associated with higher sepsis bundle adherence (adjusted odds ratio [aOR] 17.3, 95% confidence interval [CI] 6.6 to 44.9) 22 , but we subsequently found that one significant barrier to telehealth use was sepsis diagnosis and recognition. 23 In another multicenter study in telehealth-capable hospitals with contemporary controls (n=1,191), we found telehealth consultation was not associated with improved outcomes, but the subgroup of patients treated in the most remote hospitals by advanced practice providers may have had reduced mortality (aOR 0.11, 95% CI 0.02 to 0.73). 24 Since these findings were unexpected, we conducted a qualitative study of rural hospital and hub healthcare staff to better understand and interpret the findings from our quantitative studies.…”
Section: Introductionmentioning
confidence: 72%
“…5 We have previously shown that rural sepsis is underdiagnosed, however, and the failure to recognize sepsis was associated with decreased tele-ED use and higher mortality. 44,45 Filbin et al 6 identified that sepsis patients with atypical presentations were more likely to have delays in antibiotics and sepsis treatments, and they correspondingly had higher mortality. The participating tele-ED network in this study cannot screen patients for sepsis from the tele-ED hub without a telehealth consult request, so it requires local staff to recognize sepsis and request tele-ED consultation.…”
Section: Discussionmentioning
confidence: 99%